Changing relations : achieving intimacy in a time of social transition - Goodwin, Robin, 1964-; Cambridge eBooks (Cambridge : Cambridge University Press, 2009)
In a fast-changing world, what impact does social change have on our everyday relationships? How do modernisation processes influence our broader values, and how might these then affect our desires to marry, have a family and develop our social networks? And how do sudden events in a society - invasions, civil conflict, terrorist attacks, collapse of a political system - influence our relationship decisions and processes. In this book Goodwin critically reviews the literature on modernisation and contemporary relationships, challenging simplistic conclusions about the 'end of intimacy' and the inevitable decline of personal commitment. Reviewing work from across the globe, he also contends that adaptation to rapid change is moderated by individual, social class and cultural variations, with consequently differing impacts on everyday relations. In doing so he brings together contemporary debates in psychology, sociology and the political sciences on coping with social change and its impact on personal relations.
The nature of social change -- The myth of modernisation? -- More beautiful than a monkey: the achievement of intimacy -- Friends and social networks -- Sex and the modern city -- Marriage and the family -- Modelling social change and relationships.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Interpersonal relations; Intimacy (Psychology); Social networks; Social change; Electronic books